Rational design of a protein that binds integrin α(v)β(3) outside the ligand binding site - Turaga, Ravi Chakra (Nat Commun, 2016)
Integrin α(v)β(3) expression is altered in various diseases and has been proposed as a drug target. Here we use a rational design approach to develop a therapeutic protein, which we call ProAgio, that binds to integrin α(v)β(3) outside the classical ligand-binding site. We show ProAgio induces apoptosis of integrin α(v)β(3)-expressing cells by recruiting and activating caspase 8 to the cytoplasmic domain of integrin α(v)β(3). ProAgio also has anti-angiogenic activity and strongly inhibits growth of tumour xenografts, but does not affect the established vasculature. Toxicity analyses demonstrate that ProAgio is not toxic to mice. Our study reports a new integrin-targeting agent with a unique mechanism of action, and provides a template for the development of integrin-targeting therapeutics.